2004
DOI: 10.1289/ehp.6427
|View full text |Cite
|
Sign up to set email alerts
|

Application of Benzo( a )pyrene and Coal Tar Tumor Dose–Response Data to a Modified Benchmark Dose Method of Guideline Development

Abstract: Assessment of cancer risk from exposure to polycyclic aromatic hydrocarbons (PAHs) has been traditionally conducted by applying the conservative linearized multistage (LMS) model to animal tumor data for benzo(a)pyrene (BaP), considered the most potent carcinogen in PAH mixtures. Because it has been argued that LMS use of 95% lower confidence limits on dose is unnecessarily conservative, that assumptions of low-dose linearity to zero in the dose response imply clear mechanistic understanding, and that “accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…ΣPAH concentrations in these samples (5800 and 9600 mg/kg) exceed those in all of the other dust samples collected for this study. Concentrations of benzo[a]pyrene, considered the most potent carcinogen in PAH mixtures (27), in these samples are 597 and 357 mg/ kg; the median of 477 mg/kg is more than twice the median of 201 mg/kg (computed as the median of the median value for each city) in dust from sealcoated pavement for the six central and eastern cities. The median concentration of benzo[a]pyrene in the two driveway samples is 5300 times greater than the benzo[a]pyrene generic soil screening level (SSL) of 0.09 mg/kg used by the U.S. Environmental Protection Agency Superfund Program (28) and is 95 times greater than a less conservative benzo[a]pyrene soil guideline of 5 mg/kg proposed by Fitzgerald et al (27).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…ΣPAH concentrations in these samples (5800 and 9600 mg/kg) exceed those in all of the other dust samples collected for this study. Concentrations of benzo[a]pyrene, considered the most potent carcinogen in PAH mixtures (27), in these samples are 597 and 357 mg/ kg; the median of 477 mg/kg is more than twice the median of 201 mg/kg (computed as the median of the median value for each city) in dust from sealcoated pavement for the six central and eastern cities. The median concentration of benzo[a]pyrene in the two driveway samples is 5300 times greater than the benzo[a]pyrene generic soil screening level (SSL) of 0.09 mg/kg used by the U.S. Environmental Protection Agency Superfund Program (28) and is 95 times greater than a less conservative benzo[a]pyrene soil guideline of 5 mg/kg proposed by Fitzgerald et al (27).…”
Section: Discussionmentioning
confidence: 96%
“…Concentrations of benzo[a]pyrene, considered the most potent carcinogen in PAH mixtures (27), in these samples are 597 and 357 mg/ kg; the median of 477 mg/kg is more than twice the median of 201 mg/kg (computed as the median of the median value for each city) in dust from sealcoated pavement for the six central and eastern cities. The median concentration of benzo[a]pyrene in the two driveway samples is 5300 times greater than the benzo[a]pyrene generic soil screening level (SSL) of 0.09 mg/kg used by the U.S. Environmental Protection Agency Superfund Program (28) and is 95 times greater than a less conservative benzo[a]pyrene soil guideline of 5 mg/kg proposed by Fitzgerald et al (27). A summary of research on mutagenic hazards of settled house dust concluded there was "substantially elevated risk" corresponding to the 95th percentile or greater PAH content in the dust as summarized from 18 studiessthe 95th percentile concentration of benzo[a]pyrene was 13.0 mg/kg (29).…”
Section: Discussionmentioning
confidence: 96%
“…Different models may all fit the data reasonably well (top), but yield highly divergent response estimates at low doses (bottom). The data and models are taken from Fitzgerald et al (2004).…”
Section: Model Errormentioning
confidence: 99%
“…Fitzgerald et al proposed a dose-response relationship in which BaP intake at 6 mg/kg/day would induce forestomach tumors in about 90% of mice [32]. Young adult nude mice weighed around 20 g. Therefore, we selected four doses of BaP, 0, 0.2, 0.8, and 1.6 mg/week, to test the effects of BaP on xenograft tumor growth of CL1-5 cells.…”
Section: Interaction Of Bap and Estrogen On Tumor Growthmentioning
confidence: 99%